Effects of baclofen on the functional anatomy of the oesophago‐gastric junction and proximal stomach in healthy volunteers and patients with GERD assessed by magnetic resonance imaging and high‐resolution manometry: a randomised controlled double‐blind study. Issue 10 (17th September 2014) - Curcic, J.; Schwizer, A.; Kaufman, E.; Forras‐Kaufman, Z.; Banerjee, S.; Pal, A.; Hebbard, G. S.; Boesiger, P.; Fried, M.; Steingoetter, A.; Schwizer, W.; Fox, M.
Summary Background The mechanism of reflux protection may involve a 'flap valve' at the oesophago‐gastric junction (OGJ). Aim To assess the effects of baclofen, a gamma‐aminobutyric acid receptor type‐B (GABA‐B) agonist known to suppress reflux events, on the 'functional anatomy' of the OGJ and proximal stomach after a large test meal. Methods Twelve healthy volunteers (HVs) and 12 patients with gastro‐oesophageal reflux disease (GERD); with erosive oesophagitis or pathological oesophageal acid exposure completed a randomised, double‐blind, cross‐over study. On 2 test days participants received 40‐mg baclofen or placebo before ingestion of a large test meal. OGJ structure and function were assessed by high‐resolution manometry (HRM) and magnetic resonance imaging (MRI) using validated methods. Measurements of the oesophago‐gastric angle were derived from three‐dimensional models reconstructed from anatomic MRI images. Cine‐MRI and HRM identified postprandial reflux events. Mixed model analysis and Wilcoxon rank signed tests assessed differences between participant groups and treatment conditions. Results In both HVs and GERD patients, baclofen reduced the frequency of postprandial reflux events. The oesophago‐gastric insertion angle in GERD patients was reduced (−4.1 ± 1.8, P = 0.025), but was unchanged in healthy controls. In both study groups, baclofen augmented lower oesophageal sphincter (LES) pressure (HVs: +7.3 ± 1.8 mmHg, P < 0.0001, GERD: +4.50 ± 1.49 mmHg, P < 0.003) and increased LES length (HVs: +0.48 ± 0.11 cm, P < 0.0003, GERD: +0.35 ± 0.06 cm, P < 0.0001). Conclusions Baclofen inhibits transient LES relaxations and augments LES pressure and length. Additionally, baclofen has effects on the 'functional anatomy' of the OGJ and proximal stomach in GERD patients, which may suppress reflux by means of a 'flap valve' mechanism.